Combined HT7 Acupressure (Shenmen) and Murattal Therapy for Depression and Insomnia in Elderly: A Case Report - Aquino, Afnani; Susanti, Raini Diah; Pramukti, Iqbal (CV. Literasi Publikasi Indonesia, 2025)
Older adults are vulnerable to psychological disorders such as depression and insomnia, which are often interrelated and can affect both physical and emotional well-being. This study aimed to evaluate the effect of combining HT7 (Shenmen) acupressure and murattal therapy on reducing depression and insomnia in the elderly. A case report design was used, involving a 68-year-old woman residing in a social care facility who experienced severe depression and insomnia. The intervention consisted of 12 sessions over four weeks (10 minutes per session), in which the client performed self-acupressure at the HT7 point while listening to murattal as a visual-auditory calming stimulus. Depression and insomnia levels were assessed using the GDS-15 and KSPBJ-IRS instruments. Results showed a reduction in GDS-15 score from 12 to 5 (mild depression) and in KSPBJ-IRS score from 30 to 23 (mild insomnia). The client also reported emotional calmness and motivation to continue the therapy independently. This study suggests that the combined intervention is a safe and effective non-pharmacological option. Further research, such as experimental studies, is recommended with more diverse subjects and varied clinical conditions.